Chicken Primordial Germ Cell Surface Marker - Tamara J. Gough; Terry G. Wise; Matthew P. Bruce; Timothy J. Doran; Daniel S. Layton; Andrew G. D. Bean (Animals, 2025)
The creation of transgenic chickens holds significant promise for the agricultural and biotechnological sectors, offering potential improvements in disease resistance and production efficiency. The preferred method for generating gene-edited chickens involves the genetic manipulation of primordial germ cells (PGCs), making the identification and isolation of these cells a growing focus of research. PGCs are the precursors to sperm and oocytes, responsible for transmitting genetic material to the next generation. In humans, PGCs are characterized by their large size, round nuclei, and refractive lipids in the cytoplasm, and can be identified using periodic acid–Schiff (PAS) staining and the surface marker stage-specific embryonic antigen 1 (SSEA1). Similarly, chicken PGCs express SSEA1, but their most specific marker is the chicken vasa homologue (CVH), the avian equivalent of the RNA-binding factor gene vasa. However, SSEA1, along with other known surface markers, does not bind to all PGCs or lacks specificity, while CVH, although highly specific to PGCs, is intracellular and unsuitable for isolating viable cells. This study aims to develop an antibody targeting a PGC surface marker with the same specificity as CVH. Despite the importance of identifying surface markers for PGC characterization, to date, such reagents are limited. To address this, whole chicken PGCs were injected into mice, leading to the generation of a panel of monoclonal antibodies. One antibody was found to bind cultured chicken PGCs and showed reduced expression upon differentiation with retinoic acid, indicating its specificity to PGCs. Immunoprecipitation followed by mass spectrometry identified the antigen as myosin heavy chain-like (MYH9) protein. The antibody, αMYH9, was further characterized and shown to bind circulating PGCs and embryonic gonadal PGCs (Hamburger Hamilton (H-H) stage 30, embryonic day 6.5–7). Whilst our primary aim was to determine the binding to PGCs, further investigation is required to determine potential binding to somatic cells. In conclusion, this study provides the characterization of a surface marker for chicken PGCs, with significant implications for advancements in avian genetic preservation, agriculture, and biotechnology.